Aminocarbonylation of N-Containing Heterocycles with Aromatic Amines Using Mo(CO)6 - Mamone, Marius; Aziz, Jessy; Le Bescont, Julie; Piguel, Sandrine (Synthesis, 2018)
We describe herein the palladium-catalyzed aminocarbonylation of nitrogen-containing heterocycles with aniline derivatives using molybdenum hexacarbonyl as a CO solid source, expanding the scope of the limited examples. This method is compatible with a variety of substitutions on the aniline moiety. The simple reaction conditions include easily available Pd(dppf)Cl2 catalyst, DBU as base in DMF at 120 °C for 3 hours in sealed tube thereby leading to the isolation of 21 compounds with yields ranging from 18 to 82%. We also show that double aminocarbonylation reactions are possible in satisfactory yields regarding both coupling partners.
Keywords: heterocycles; nitrogen; aromatic amines; amide; carbonylation; palladium; catalysis